Hubungan Ketuban Pecah Dini Dengan Perpanjangan Kala I Fase Aktif Di Bps Suhartatik, S.St - Kinanatul Qomariyah; Dewi Susanti Oktavia (Universitas Islam Madura, 2021)
Based on data from the International NGO Forum on Indonesia Development (INFID) in 2013, the incidence of prolongation of the first stage of the active phase in Indonesia was 5% of all causes of maternal death. In BPS Suhartatik, S.ST, in 2013 there were 63 (53.8%) mothers who gave birth experienced an extension of the first stage of the active phase, and increased in 2014 as many as 76 (61.29%) of mothers who gave birth experienced an extension of the first phase of the active phase that was wrong one of the biggest causes is premature rupture of membranes. The purpose of this study was to determine the relationship between premature rupture of membranes and the extension of the first stage of the active phase at BPS Suhartatik, S.ST. The design of this research is correlative analytic. Meanwhile, based on time, this study is a cross sectional study. The total population is 34 with the sampling technique using saturated sampling. The independent variable in this study is premature rupture of membranes, while the dependent variable is the extension of the first stage of the active phase. Data were collected using partograph and observation sheet. The statistical test used was chi-square. Based on the cross tabulation, most of the women who gave birth did not experience premature rupture of membranes and extended phase I of the active phase, after being analyzed using the chi-square statistical test, the results obtained were X2count (6.69)> X2table (3.841) so it could be concluded that there was a relationship between ruptured membranes. early stage with an active phase I extension at BPS Suhartatik, S.ST. Maternity women who experience prolonged phase I of the active phase due to premature rupture of membranes can be prevented by regular pregnancy checks, following pregnancy exercises, and attending posyandu every month. In addition, mothers also need to know the signs and symptoms of premature rupture of ketuban